PENGETAHUAN DAN TINDAKAN PERAWAT DALAM PENANGANAN PASIEN DENGAN PENYAKIT JANTUNG KORONER DI IGD RSUD DR MM DUNDA LIMBOTO - Pipin Yunus; Haslinda Damansyah (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
ABSTRACTThis research was conducted at IGD RSUD Dr MM Dunda Limboto. The aim of this research was to know the relationship of knowledge and actions of nurses in the treatment of patients with CHD. This research method using cross sectional research design, with a total sample of 26 people. Measuring tool used is the observation sheet and questionnaire sheet. The research result shows the chi-square test p value = 0.028 which is smaller than α (0.05), then Ho is rejected Ha is received, so that shows that there has a relationship between knowledge and action of nursing in the treatment of patients with CHD in IGD RSUD. Dr. MM Dunda Limboto.